2009
DOI: 10.1155/2010/795804
|View full text |Cite
|
Sign up to set email alerts
|

Anti Epileptic Activity of Morinda citrifolia Linn Fruit Extract

Abstract: Fruit extract ofMorinda citrifolia(Noni), a medicinal plant used in many neuro protective ayurvedic preparations was evaluated for its protective effect against seizures induced by Maximal Electro Shock (MES) method in rats. A daily dose of 200 and 400 mg/kg of the extract was administered to the animals for 15 days, after which seizures were induced by maximum electro shock method and the duration of various phases of epileptic attacks were recorded and compared with the control animals. A significant (P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…It was found that the reduction in these neurotransmitters including noradrenaline in the amygdala and the hippocampus, serotonin in the amygdala, DOPAC in the hippocampus and the substantia nigra, and HVA in the substantia nigra of the noni group might be responsible for anxiolytic effects of noni juice [ 8 ]. Conversely, it has been demonstrated that ethyl acetate fraction of crude methanol extract of M. citrifolia at a daily dose of 200 and 400 mg/kg which was administered to the rats for 15 days significantly increased the brain levels of serotonin, dopamine, and noradrenaline [ 7 ]. This opposing effect of noni on monoamine levels in two different studies could be due to the difference in the doses of noni used for these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the reduction in these neurotransmitters including noradrenaline in the amygdala and the hippocampus, serotonin in the amygdala, DOPAC in the hippocampus and the substantia nigra, and HVA in the substantia nigra of the noni group might be responsible for anxiolytic effects of noni juice [ 8 ]. Conversely, it has been demonstrated that ethyl acetate fraction of crude methanol extract of M. citrifolia at a daily dose of 200 and 400 mg/kg which was administered to the rats for 15 days significantly increased the brain levels of serotonin, dopamine, and noradrenaline [ 7 ]. This opposing effect of noni on monoamine levels in two different studies could be due to the difference in the doses of noni used for these studies.…”
Section: Discussionmentioning
confidence: 99%
“…significantly decreased the apomorphine-induced cage climbing behaviour and methamphetamine-induced stereotypy behaviour in mice in a dose-dependent manner which demonstrated the antidopaminergic effect of noni fruit extract [ 6 ]. Furthermore, it was also reported that the administration of M. citrifolia fruit extract significantly increased the brain levels of serotonin, dopamine, and noradrenaline in rats [ 7 ]. Similarly, other neurochemical analysis of noni-treated rats (1 mL/day, p.o.)…”
Section: Introductionmentioning
confidence: 99%
“…M. citrifolia fruit extract possesses protective effects against seizures induced by maximal electro shock in the rats. The noni juice administration regulates dopamine, serotonin and noradrenaline levels in forebrain region of epileptic patients (Muralidharan & Srikanth, ). The leaf extracts of M. citrifolia increases stamina by decreasing levels of blood lactate and blood urea nitrogen.…”
Section: Pharmacology Of Indian Morinda Speciesmentioning
confidence: 99%
“…11 In our past study we reported the antiepileptic activity of Morinda citrifolia Linn fruit extract against seizures instigated by Maximal Electro Shock (MES) technique in rats. 12 Köktürk et al assessed the neuroprotective impacts of Morinda citrifolia L. (Rubiaceae), regularly known as Noni, and memantine on hydrocephalus-actuated neurodegenerative disorders. 13 Pandy et al showed the antidopaminergic impact of Morinda citrifolia Linn.…”
Section: Introductionmentioning
confidence: 99%